Leaf your Chair Behind - Calm Persuasion for Frequent Sitting Breaks Among Office-Workers - Jung-Krenzer, Theresa; Kirchner-Krath, Jeanine; Retz, Celina; Altmeyer, Maximilian (ACM International Conference Proceeding Series, 2024)
Sedentary behavior has been linked to numerous detrimental health outcomes. This is particularly pronounced among office workers. Sitting breaks can attenuate some of these detrimental health effects. Thus, our goal was to design a persuasive system to prompt frequent sitting breaks in the office. With our system we want to address two key issues of existing approaches: low compliance due to lack of motivation, and user annoyance with frequent prompts. Based on a literature review, we developed four design concepts each using a different prompt modality (appearance, audio, light, movement) and evaluated them qualitatively by conducting a focus group interview with a panel of workplace health management experts (N=5) and quantitatively in an explorative online study with our target demographic (N=39) rating the concepts' perceived persuasiveness and obtrusiveness. Based on our findings, we derive design implications for researchers and practitioners, and demonstrate their technical feasibility by providing a proof-of-concept implementation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: calm technology; office; persuasive technology; sedentary behavior